Fibroblast-derived matrix (FDM) as a novel vascular endothelial growth factor delivery platform - Du, Ping; Hwang, Mintai P.; Noh, Yong Kwan; Subbiah, Ramesh; Kim, In Gul; Bae, Soon Eon; Park, Kwideok (ELSEVIER SCIENCE BV, 2014)
Vascular endothelial growth factor (VEGF) is one of the most important signaling cues during angiogenesis. Since many delivery systems of VEGF have been reported, the presentation of VEGF using a more physiologically relevant extracellular matrix (ECM), however, has yet to be thoroughly examined. In this study, we propose that fibroblast-derived extracellular matrix (FDM) is a novel platform for angiogenic growth factor delivery and that FDM-mediated VEGF delivery can result in an advanced angiogenic response. The FDMs, activated by EDC/NHS chemistry, were loaded with varying amounts of heparin. Different doses of VEGF were subsequently immobilized onto the heparin-grafted FDM (hep-FDM); 19.6 +/- 0.6, 39.2 +/- 3.2, and 54.8 +/- 8.9 ng of VEGF were tethered using 100, 300, and 500 ng of initial VEGF, respectively. VEGF-tethered FDM was found chemoattractive and VEGF dose-dependent in triggering human umbilical vein endothelial cells (ECs) migration in vitro. When hep-FDM-bound VEGF (H-F/V) was encapsulated into alginate capsules (A/H-F/V) and subjected to release test for 28 days, it exhibited a significantly reduced burst release at early time point compared to that of A/V. The cell proliferation results indicated a substantially extended temporal effect of A/H-F/V on EC proliferation compared to those treated with soluble VEGF. For a further study, A/H-F/V was transplanted subcutaneously into ICR mice for up to 4 weeks to assess its in vivo effect on angiogenesis; VEGF delivered by hep-FDM was more competitive in promoting blood vessel ingrowth and maturation compared to other groups. Taken together, this study successfully engineered an FDM-mediated VEGF delivery system, documented its capacity to convey VEGF in a sustained manner, and demonstrated the positive effects of angiogenic activity in vivo as well as in vitro. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: EXTRACELLULAR-MATRIX; ALGINATE HYDROGELS; IN-VITRO; VEGF; ANGIOGENESIS; HEPARIN; BINDING; NEOVASCULARIZATION; SCAFFOLDS; PROTEINS